Discussion on the Dynamics of Urban Transformation: The Case Study of Kadikoy, Istanbul - Akin, Oya (UNIV POLITECNICA CATALUNYA, 2022)
The accumulation and circulation of capital, in other words the neoliberal urbanization, has transformed urban areas dramatically in an unrecognisable and unlimited way without considering any geography, culture and national boundaries. Turkish cities have experienced this process of dramatic urban transformation. The state has played a crucial role in the dramatic transformation of urban area, providing incentives and subsidies to developers through legislations, tax reliefs, etc. This paper explores the roe of state subsidies in the transformation of Kadikoy district in Istanbul. A law was introduced in 2012. The law has led to the dramatic and accelerated transformation of urban areas in Istanbul, in the Kadikoy district. The aim of this law is to attract entrepreneurs to build up areas, through subsidies, such as tax reductions, additional construction rights and rent aids for flat owners. This transformation has taken place at a parcel-scale with multiple ownership through demolition and reconstruction. It focused on built up areas in the risk of earthquake with unsound houses. However, urban regeneration did not take place in these areas with earthquake risk, as defined in the law, instead it took place in areas where entrepreneurs could gain the maximum profit in the Kadikoy District. The Kadikoy district has experienced this accelerated and dynamic process of urban regeneration within the boundaries of Istanbul City. This article therefore investigates the dynamics of urban regeneration in the Kadikoy District: the role of the state, land and property values, the availability of mortgages, entrepreneurs profit levels and the wants and desires of buyers.
Keywords: Neoliberalism; urban transformation; State; finance; GENTRIFICATION; GOVERNANCE; POLITICS; CITIES; Architecture; Urban Studies